El Excentrico, 1961-01-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 20, 1961 [5 de enero de 1961]. Ano 11, No 7. Cover has a photograph of celebrity known as, "Daddy O" with headline "Three faces of Daddy O by staff photographer Bert Garcia, Jr."